2022
DOI: 10.1021/acs.chemmater.1c03503
|View full text |Cite
|
Sign up to set email alerts
|

CeTaN3 and CeNbN3: Prospective Nitride Perovskites with Optimal Photovoltaic Band Gaps

Abstract: Perovskites constitute an exceptionally tunable materials family with diverse applications in electronics, optoelectronics, energy, and quantum technologies. Out of the thousands of known perovskites, the majority of compounds are oxides, halides, and chalcogenides. In contrast, only two nitride perovskites are currently known. In this work we perform a thorough ab initio computational screening of possible nitride perovskites, and we identify two new compounds, CeNbN 3 and CeTaN 3 , with band gaps in the near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 121 publications
0
17
0
Order By: Relevance
“…LaWN 3 , which is predicted and calculated to be thermodynamically stable in this work, was successfully synthesized in a recent report . A recent computational study also reports the stabilities of CeTaN 3 , CeNbN 3 , CeWN 3 , and CeMoN 3 in perovskite structures …”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…LaWN 3 , which is predicted and calculated to be thermodynamically stable in this work, was successfully synthesized in a recent report . A recent computational study also reports the stabilities of CeTaN 3 , CeNbN 3 , CeWN 3 , and CeMoN 3 in perovskite structures …”
Section: Resultsmentioning
confidence: 66%
“…17 A recent computational study also reports the stabilities of CeTaN 3 , CeNbN 3 , CeWN 3 , and CeMoN 3 in perovskite structures. 6 From this evaluation, the compounds LaWN 3 , LaMoN 3 , CeWN 3 , CeMoN 3 , YWN 3 , and YMoN 3 were prioritized for experimental testing because of their calculated stabilities (ΔH d < 0) and to provide variety across both A-and B-site cations; it should be noted that perovskite LaWN 3 has already been successfully synthesized 17 and was included here for validation purposes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8] Moreover, prediction of properties such as ferroelectricity in LaWN 3 , suitable bandgaps for photovoltaics in CeMN 3 (M = Ta, Nb), as well as hard ferromagnetism in RReN 3 , sparked interest in these materials. [8][9][10] However, synthesized nitride perovskites ABN 3 are scarce and to date only three materials are reported: bulk-phase ThTaN 3 from 1995, thin-film LaWN 3 with a polar structure from 2021, and bulk-phase LaReN 3 from 2021. [11][12][13] These few reports reflect synthetic challenges rooted in the low formation energies of transition metal nitrides.…”
Section: Introductionmentioning
confidence: 99%
“…Nitride perovskites ABN 3 have recently gained much attention as theoretical studies have suggested stable compositions based on early heavy transition metals as B‐cations with rare‐earths (R) occupying the A‐sites [7,8] . Moreover, prediction of properties such as ferroelectricity in LaWN 3 , suitable bandgaps for photovoltaics in CeMN 3 (M=Ta, Nb), as well as hard ferromagnetism in RReN 3 , sparked interest in these materials [8–10] . However, synthesized nitride perovskites ABN 3 are scarce and to date only three materials are reported: bulk‐phase ThTaN 3 from 1995, thin‐film LaWN 3 with a polar structure from 2021, and bulk‐phase LaReN 3 from 2021 [11–13] …”
Section: Introductionmentioning
confidence: 99%